Effect of Hydrological Connectivity on the Phosphorus Buffering Capacity of an Urban Floodplain - Preiner, Stefan; Bondar-Kunze, Elisabeth; Pitzl, Beate; Weigelhofer, Gabriele; Hein, Thomas (Frontiers in Environmental Science, 2020)
Floodplains can perform nutrient buffering functions and therefore influence the riverine nutrient dynamics depending on the extent of the hydrological connectivity. This work focused on quantifying the adsorption/desorption potential of a degraded floodplain of the Danube River (Lower Lobau) based on sediment characterization (grain size distribution, organic content, and P-fractions) and sediment type-specific P-adsorption via batch experiments. We established an adsorption/desorption budget model with a high temporal and spatial resolution. With this model, we identified spatial patterns related to hydrology and calculated the phosphorus buffering capacity of permanent and temporary floodplain water bodies. Sediment characteristics were defined by the distance to the inflow area and the hydrological connectivity of the floodplain water bodies. The main factor for the concentration of total phosphorus (Ptot) in the sediments was the grain size distribution. Ptot was ten times higher in silt-dominated sediments compared to gravel-dominated sediments. Inorganic phosphorus (Pinorg) ranged between 36 and 90% depending on the organic content of the sediments. Both the adsorption and the desorption potential of SRP (soluble reactive phosphorus) were highest in large, frequently connected water bodies and were strongly controlled by hydrology. The total adsorption potential of the floodplain was up to 40 times higher in wet years (e.g., 2002) than in dry years (e.g., 2003), when floodplain water bodies were connected less frequently to the main channel of the Danube. Up to 75% of the adsorbed SRP was desorbed and released into the water column after periods of connection. Consequently, SRP adsorption directly reduced the P-load in the Danube River main channel. The adsorption/desorption mechanisms worked as a buffering system by taking up the SRP imported during floods and releasing it over a longer period after the floods. This stimulated high primary production in the floodplain water bodies and impacted the overall P-retention of the floodplain.